PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA UNTUK PENGEMBANGAN UMKM MELALUI ONLINE SINGLE SUBMISSION (OSS) DI KELURAHAN SURYA TIMUR, KABUPATEN BANGKA - Tipani, Reza; Afriyanti, Zeby Melani; Susanti, Lia; Syakila, Puput; Sihamat, Jhodi Adi; Lavania, Delvi; Dalimunthe, Desy Yuliana (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
One very important aspect in the development of Micro, Small and Medium Enterprises (MSMEs) is business legality. Community service activities related to assistance in creating business legality through Business Identification Numbers (NIB) and Home Industry Food Production Certificates (SPP-IRT) are aimed at MSMEs in East Surya Village, Bangka Regency. The aim of this activity is to provide assistance to East Surya Subdistrict MSMEs regarding creating accounts and procedures for processing legalities through Online Single Submission (OSS). The method for implementing this service activity is divided into three stages, namely observation, counseling regarding NIB and SPP-IRT, and implementation of mentoring. The number of MSMEs that have been recorded by the UBB Surya Timur KKN-T team is 19 MSMEs and 5 MSMEs have successfully created NIBs and 1 SPP-IRT person. This process takes 14 days. The availability of legality for MSME actors is very important for the existence and development of MSMEs considering that the NIB is an identification mark for every business actor, both individual and non-individual businesses. By having a Business Identification Number and a Home Industry Food Production Certificate, MSMEs have valid identification in carrying out their business activities, so that they can obtain legitimacy and official recognition from the government. The various benefits obtained from the existence of NIB and SPP-IRT help MSME players in developing their products, in this case in the form of consumer and business partner confidence in the product as well as increasing the self-confidence of MSME players to be more competitive in developing business products and the type of business they run.